Idiopathic Non‐task‐Specific Upper Limb Dystonia, a Neglected Form of Dystonia. Issue 11 (14th July 2020) - Defazio, Giovanni; Ercoli, Tommaso; Erro, Roberto; Pellicciari, Roberta; Mascia, Marcello Mario; Fabbrini, Giovanni; Albanese, Alberto; Lalli, Stefania; Eleopra, Roberto; Barone, Paolo; Marchese, Roberta; Ceravolo, Roberto; et al.
Abstract: Objective: The objective of this study was to describe the clinical and demographic features of idiopathic non‐task‐specific upper limb dystonia compared with the task‐specific form. Methods: In this retrospective study, adult patients with idiopathic upper limb dystonia, either focal or as part of a segmental/multifocal dystonia, from the Italian Dystonia Registry were enrolled. In patients with focal upper limb dystonia, dystonia spread was estimated by survival analysis. Results: Of the 1522 patients with idiopathic adult‐onset dystonia included in the Italian Dystonia Registry, we identified 182 patients with upper limb dystonia. Non‐task‐specific dystonia was present in 61.5% of enrolled cases. Women predominated among non‐task‐specific patients, whereas men predominated in the task‐specific group. Peak age of upper limb dystonia onset was in the sixth decade in the non‐task‐specific group and in the fourth decade in the task‐specific group. In both groups, upper limb dystonia started as focal dystonia or as part of a segmental dystonia. Segmental onset was more frequent among non‐task‐specific patients, whereas focal onset predominated among task‐specific patients. Dystonic action tremor was more frequent among non‐task‐specific patients. No significant differences between groups emerged in terms of sensory trick frequency, rest tremor, or family history of dystonia. In patients with focal upper limb dystonia, dystonia spread was greater in the non‐task‐specific group. Conclusion: Novel information on upper limb dystonia patients suggests that non‐task‐specific and task‐specific upper limb dystonia have different demographic and clinical features. However, it remains to be determined whether these differences also reflect pathophysiological differences. © 2020 International Parkinson and Movement Disorder Society